INNOVATIVE METHODS OF IMPROVING THE PROFESSIONAL SKILLS OF A TEACHER OF PHYSICAL CULTURE - Uraimov Sanjar; Husanov Doston (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article highlights the worldview, spiritual, communicative, volitional, intellectual, movement, but personal qualities and physical health of teachers of physical culture, as well as information such as physical health, temperance, resourcefulness, initiative, mental capacity.